Anthropometry and Dietary Intake before and during a Competition in Mountain Runners. (7th August 2014) - Carlsohn, Anja; Müller, Wolfram
Abstract : Mountain running is a non-Olympic sport consisting of uphill or up- and downhill races at moderate-to-high altitude. Special nutritional requirements are anticipated, but no nutritional data of mountain runners are available. In three studies, physique of elite and recreational athletes (N = 62 ), maximum oxygen uptake (N = 3 ), and prerace and race day dietary intake (N = 6 ) were measured (mean ± SD). Mean oxygen uptake was68.7 ± 5.2  mL/kg/min. Energy and carbohydrate intake before a race (29 ± 15  km, 1596 ± 556  m HD) was3199 ± 701  kcal/d (13.4 ± 2.9  MJ/d) and497 ± 128  g/d (8.3 ± 1.8  g/kg/d) in German national team members. Fluid intake was calculated as2783 ± 1543  mL/d. During the race, athletes consumed336 ± 364  kcal and927 ± 705  mL of fluids. Substrate intake per hour was calculated as23 ± 22  g of carbohydrates and4.0 ± 3.2  g of proteins. In conclusion, anthropometric and oxygen uptake characteristics of mountain runners were similar to those reported for elite distance runners. Carbohydrate intake before and during the race was below recommendations for endurance athletes. This is of concern when considering the increased reliance on carbohydrates at altitude.